Dynamic Optimization and Production Planning of Thermal Cracking Operation - Emil H. Edwin; Jens G. Balchen (Modeling, Identification and Control, 2003)
This work addresses the dynamic optimization of the production period of thermal crackers with respect to coke formation in the cracking coil and transfer line exchanger. Optimal time dependent trajectories of feed rate, steam to hydrocarbon ratio, and reaction severity are calculated. The net earnings based on the price of hydrocarbons, kid, steam, decoking, and maintenance cost are maximized. All important operational constraints are included and the optimization problem is solved using parameterized free variable trajectories (piece wise constant) and a standard SQP package. Rigorous distributed physical models are used and calculation show that dynamic optimization gives up to 2( earnings - expenses) than conventional steady state optimization performed on the same models. This is in the same range as earnings reported from steady state optimization implementations alone.